Supporting colleagues to improve care: educating for quality improvement. Issue 4 (23rd December 2014) - Runnacles, Jane; Roueché, Alice
Abstract : Clinicians at the front line of healthcare delivery are very well positioned to identify and improve the system in which they work. Training curricula, however, have not always equipped them with the skills or knowledge to implement change. This article looks at educational approaches to support clinicians to be actively involved with quality improvement (QI). It looks at the role of doctors in postgraduate training (DrPGT) and their educational supervisors and builds on the topics discussed throughout the 'EQUIPPED' article series. Factors for success of a QI education programme and practical ideas for overcoming barriers to supporting clinicians in QI are discussed. We present examples of educational initiatives and a framework for evaluating such programmes, and we examine the role of faculty development to help inspire and support colleagues to improve care.